Non-secretory myeloma in young man mimicking the Gorham disease: case report and the literature review - Ferjani Hanene Lassoued; Mariem Moalla; Affess Hassen; Maatallah Kaouther; Kaffel Dhia; Jenzri Mourad; Hamdi Wafa (Sciendo, 2022)
Multiple myeloma is a neoplasm of plasma cells affecting mostly the elderly with incidence peaks between 60 and 70 years. This disease is exceedingly rare in younger people, especially in adults under 30-year-old. Non-secretory multiple myeloma accounts for 1-5% of all cases of multiple myeloma. It is also a rare condition in young adult patients, and only six cases have been reported [1]. We herein describe a rare case of non-secretory myeloma in a 22-year-old male, explaining from chest wall pain, without general manifestation. Plain radiography and CT scans revealed diffuse osteolytic lesion mimicking the Gorham disease. A bone marrow biopsy was conducted, revealing the diagnosis of myeloma.